An improved separation procedure for nucleoside monophosphates on polyethyleneimine-(PEI-)cellulose thin layers. - Gupta, R C (1976)
A procedure is described for the two-dimensional separation of the 4 major and 16 modified nucleoside-(5') monophosphates on anion-exchange thin layers of polyethyleneimine- (PEI-)cellulose. The method, which is simple and less time-consuming than existing partition chromatographic methods, may be used for the identification of 5'-termini of RNA and RNA fragments.